The Influence of Performance Appraisals on Employee Work Motivation at the Gowa Regency Trade and Industry Service - Risaldi (Journal GoodWill, 2024)
Employee performance appraisals play a crucial role in enhancing organizational effectiveness by influencing individual motivation and work behavior. This study aims to examine the effect of performance appraisals on employee work motivation at the Trade and Industry Department of Gowa Regency, Indonesia. A quantitative research design was employed using a total sampling technique with a population and sample of 35 employees. Data were collected through structured questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) version 23. The results of the simple linear regression analysis indicate that performance appraisal has a positive and significant effect on employee work motivation, as shown by a significance value of 0.000 (< 0.05) and a calculated t-value of 5.004 > t-table value of 1.692. This finding implies that effective performance evaluation systems—emphasizing indicators such as attendance, honesty, responsibility, and cooperation—can substantially improve employees’ motivation to achieve organizational goals. The study reinforces McClelland’s theory of needs, which posits that motivation arises from the drive for achievement, affiliation, and power. The results also align with previous empirical evidence that performance appraisal is a determinant of work motivation in public organizations. It is recommended that management at the Trade and Industry Department of Gowa Regency strengthen the implementation of performance appraisal systems and provide consistent feedback and recognition to enhance employee motivation and overall organizational performance.